Dialogues of the Dead - Lyttelton, George Lyttelton, Baron, 1709-1773; Montagu, Mrs. (Elizabeth), 1718-1800; Morley, Henry, 1822-1894 (Salt Lake City, UT : Project Gutenberg, 2006)
"Dialogues of the Dead" by Lord George Lyttelton is a philosophical work composed of dialogues written in the 18th century. This collection employs a dramatic format to explore timeless truths about human existence, virtue, and politics through conversations between historical and legendary figures, such as Lord Falkland and Mr. Hampden. The dialogues are characterized by a reflection on moral values and the complexities of human character, encouraging readers to ponder the moral implications of their actions and beliefs. The opening of the text introduces the first dialogue between Lord Falkland and Mr. Hampden, discussing their perspectives on the civil unrest of their time and reflecting on the moral consequences of their actions in support of either monarchy or the Commonwealth. They explore themes of loyalty, virtue, and the tragic outcomes of their political struggles, demonstrating how personal and political beliefs can intertwine, leading to profound consequences in life and death. Through their discussions, the author sets the stage for a deeper examination of ethical dilemmas faced by individuals in power, inviting readers to consider the relevance of these discussions to their own lives. (This is an automatically generated summary.)
I. Lord Falkland; Mr. Hampden -- II. Louis le Grand; Peter the Great -- III. Plato; Fenelon -- IV. Mr. Addison; Dr. Swift -- V. Ulysses; Circe -- VI. Mercury; An English Duellist; A North-American Savage -- VII. Pliny the Elder; Pliny the Younger -- VIII. Fernando Cortez; William Penn -- IX. Marcus Portius Cato; Messalla Corvinus -- X. Christina, Queen of Sweden; Chancellor Oxenstiern -- XI. Titus Vespasianus; Publius Cornelius Scipio Africanus -- XII. Henry Duke of Guise; Machiavel -- XIII. Virgil; Horace; Mercury; Scaliger the Elder -- XIV. Boileau; Pope -- XV. Octavia; Portia; Arria -- XVI. Louise de Coligni, Princess of Orange; Frances Wasingham, Countess of Essex and of Clanricard; before, Lady Sidney -- XVII. Marcus Brutus; Pomponius Atticus -- XVIII. William the Third, King of England; John De Witt, Pensioner, of Holland -- XIX. M. Apicius; Darteneuf -- XX. Alexander the Great; Charles the Twelfth, King of Sweden -- XXI. Cardinal Ximenes; Cardinal Wolsey -- XXII. Lucian; Rabelais -- XXIII. Pericles; Cosmo de Medicis, the first of that Name -- XXIV. Locke; Bayle -- XXV. Archibald, Earl of Douglas, Duke of Touraine; John, Duke of Argyle and Greenwich, Field-Marshal of His Britannic Majesty's Forces -- XXVI. Cadmus; Hercules -- XXVII. Mercury; And a modern fine Lady -- XXVIII. Plutarch; Charon; And a modern Bookseller.
Dialogues XXVI-XXVIII are by Elizabeth Montagu.
Release date is 2006-02-03
Transcribed from the 1889 Cassell & Company edition by David Price
Keywords: Imaginary conversations; Dialogues, English -- Early works to 1800